Determination of growth regimes of Pd nanostructures on c-plane sapphire by the control of deposition amount at different annealing temperatures. Issue 23 (31st May 2017) - Kunwar, Sundar; Sui, Mao; Pandey, Puran; Zhang, Quanzhen; Li, Ming-Yu; Bhandari, Harish; Lee, Jihoon
Abstract : Semi-spherical and irregular Pd nanoparticles and voids are fabricated on sapphire(0001) by the solid-state dewetting of sputter-deposited Pd thin films at different thickness and temperature. The structural evolution, surface morphology transformation and optical properties of Pd nanostructures are probed. Abstract : Metallic nanoparticles (NPs) with tunable physical, optical and catalytic properties have a wide range of applications including various optoelectronics, sensors and fuel cells. In this paper, we demonstrate the evolution of various physical properties, configurations, size and density of palladium (Pd) nanostructures on sapphire(Al2 O3 ) (0001) by the systematic control of deposition amount (DA) at distinct annealing temperatures. The transformation of the deposited thin films into various Pd NPs is achieved by the dewetting of the thin film by means of surface diffusion, nucleation, Volmer–Weber growth and surface energy minimization mechanism. Depending on the evolution of size, density and configuration, five distinctive regimes of Pd nanostructures are demonstrated: (i) nucleation and evolution of small NPs between 1 and 3 nm, (ii) medium NPs with the dominating vertical growth between 5 and 20 nm, (iii) laterally expanded large NPs between 30 and 40 nm, (iv) irregular coalesced Pd NPs between 50 and 80 nm and (v) voids evolution between 100 and 200 nm. Initial film thickness and annealing temperature play major roles on the dewetting process and the resulting Pd nanostructures are notably distinguished. The fabricated Pd nanostructures influence the lattice vibration modes of sapphire(0001) such as gradual decrement in the intensity and left-shift of the peak position with increased surface coverage. In addition, the optical properties are studied by UV-VIS-NIR (300–1100 nm) reflectance spectra, which shows the reflectance, absorption and scattering over the wavelength and are closely related to the morphology evolution of Pd nanostructures.